1982
DOI: 10.1192/bjp.141.5.503
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Psychiatric In-Patients

Abstract: SummarySuicide risks for psychiatric hospital in-patients may be described by empirical relationships that take account of sex, length of admission and diagnosis. Risks are highest in males, in the first week of admission, and in depressed patients. Hospital suicide rates do not follow the same pattern as those for the general population and it is suggested that this effect may be the result of current selection procedures. The standard mortality ratio, which compares hospital with general population suicides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 13 publications
9
37
0
1
Order By: Relevance
“…This ®gure is comparable to 15% reported in the only speci®c study of psychogeriatric inpatient suicides (Modestin, 1989), to a range of 3±12% reported in other studies (Sletten et al, 1972;Goh et al, 1989) and the observation that inpatient suicide rates do not increase with age (Copas and Robin, 1982). Thus, elderly patients appear under-represented among inpatient suicides.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This ®gure is comparable to 15% reported in the only speci®c study of psychogeriatric inpatient suicides (Modestin, 1989), to a range of 3±12% reported in other studies (Sletten et al, 1972;Goh et al, 1989) and the observation that inpatient suicide rates do not increase with age (Copas and Robin, 1982). Thus, elderly patients appear under-represented among inpatient suicides.…”
Section: Discussionsupporting
confidence: 89%
“…The retrospective study design and the absence of data on other causes of death did not allow examination of this hypothesis. Second, inpatient psychogeriatric populations include substantial numbers of dementia patients who are unlikely to commit suicide (Copas and Robin, 1982). The association between`alive' psychogeriatric patients and dementia approach signi®cance and is consistent with this observation.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Different recent studies have reported inpatient suicide rates varying between 70 and 270 per 100 000 psychiatric admissions (Deisenhammer et al 2000;Powell et al 2000;Dong et al 2005;Neuner et al 2008;Madsen et al 2012). Suicide risk was also noted to be more both immediately after admission and immediately following discharge and as well as in the case of short duration of inpatient treatment (Copas & Robin, 1982;Rossau & Mortensen, 1997;Qin & Nordentoft, 2005;Hunt et al 2013). It has been noted that majority of the in-patient suicides occurred at a time that was thought to have no/ low risk of suicide (Dong et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Deaths of patients under psychiatric care, especially if they are in-patients, have been the subject of a number of retrospective studies (Copas & Robin, 1982;Morgan & Priest, 1991;Modestin et al, 1992;Roy & Draper, 1995;Proulx et al, 1997). They have also been a particular focus of the National Confidential Inquiry (Appleby et al, 1999) as well as many individual inquiries.…”
mentioning
confidence: 99%